Effects of low-level laser irradiation on proliferation and functional protein expression in human RPE cells. Issue 9 (December 2015) - Dang, Yalong; Wu, Wentao; Xu, Yongsheng; Mu, Yalin; Xu, Ke; Wu, Haotian; Zhu, Yu; Zhang, Chun
Abstract Low-level laser irradiation (LLLI) modulates a set of biological effects in many cell types such as fibroblasts, keratinocytes, and stem cells. However, no study to date has reported the effects of LLLI on retinal pigment epithelia (RPE) cells. The aim of this study was to investigate whether LLLI could enhance the proliferation of RPE cells and increase the expression of RPE functional genes/proteins. Human ARPE-19 cells were seeded overnight and treated with 8 J/cm2 of LLLI. Cell proliferation was measured by CCK8 assay and cell cycle distribution was evaluated by FACS. The transcription of cell cycle-specific genes and RPE functional genes was quantified by RT-PCR. Moreover, the expression of ZO-1 and CRALBP were evaluated by immunostaining. A dose of 8 J/cm2 of LLLI significantly increased proliferation and promoted cell cycle progression while upregulating the transcription ofCDK4 andCCND1 and decreasing the transcription ofCDKN2A, CDKN2C, andCDKN1B in human ARPE-19 cells. Additionally, LLLI enhanced the expression of ZO-1 and CRALBP in human ARPE-19 cells. In conclusion, LLLI could enhance the proliferative ability of human ARPE-19 cells by modulating cyclin D1, CDK4, and a group of cyclin-dependent kinase inhibitors. It also could increase the expression of RPE-specific proteins. Thus, LLLI may be a potential approach for the treatment of RPE degenerative diseases.